Friend or fiend? with the Pain and the Great One - Blume, Judy (Delacorte Press, 2009)
First-grader Jake "The Pain" and his sister, third-grader Abigail "The Great One" have more adventures, including visiting their cousins in New York and celebrating their cat Fluzzy's birthday.